Strategies for Improving the Competitiveness of MSMEs through the Utilisation of Information and Communication Technology - Arjang Arjang; Sutrisno Sutrisno; Riko Mersandro Permana; Ratih Kusumastuti; Abu Muna Almaududi Ausat (Al-Buhuts, 2023)
The purpose of this study is to identify factors that influence the use of ICT by MSMEs, analyse the effect of ICT use on the competitiveness of MSMEs, and develop appropriate strategies to improve the use of ICT by MSMEs. This research is qualitative in nature. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. This study found that ICT utilisation can be an important strategy in improving the competitiveness of MSMEs. In its utilisation, MSMEs can utilise ICT to improve efficiency and effectiveness in business management, expand their market, and improve brand and product promotion more efficiently and effectively. The government and private sector need to play an active role in providing adequate access and technology infrastructure, providing training and guidance for MSMEs, as well as providing online platforms and encouraging collaboration between MSMEs